KONFLIK DAN PENYELESAIAN WARISAN DALAM MASYARAKAT ADAT DESA BATUATAS TIMUR KECAMATAN BATUATAS KABUPATEN BUTON SELATAN: PENDEKATAN MAQASHID SYARIAH - Hasnidar, Hasnidar; Purnamayanti, Irma; Haniru, Rahmad (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to analyze inheritance conflicts and their resolution mechanisms within the customary community through the perspective of maqashid sharia. The research focuses on the interacti on between customary law and Islamic law, as well as their implicatio ns for social justice and community harmony. The findings reveal that inheritance conflicts in Batuatas Timur generally arise from differenc es in perceptions regarding asset distribution, particularly between customary principles and Islamic legal norms. However, the resolution process is carried out through deliberation involving customary leade rs and religious figures, resulting in decisions that are not only conside red just according to local customs but also possess moral legitimacy in accordance with Islamic law. This process demonstrates a synergy between customary and Islamic law, which contrasts with previous studies that highlighted the dominance of one legal system over the other. The research employs a qualitative method with a case study approach. Data were collected through direct observation of inheritan ce distribution practices, indepth interviews with customary leaders, religious authorities, and community figures, as well as documentation from village archives and records.